2008
DOI: 10.1038/ncpgasthep1001
|View full text |Cite
|
Sign up to set email alerts
|

A case of vanishing bile duct syndrome and IBD secondary to Hodgkin's lymphoma

Abstract: The initial symptoms were managed with budesonide, but following recurrence, the patient's underlying lymphoma was treated with nitrogen mustard and dexamethasone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The disappearance of the bile ducts is a common mechanism for different diseases due to multiple pathologies 2. Conditions which initiate this kind of bile duct destruction could be congenital, idiopathic, toxin or drug induced, infectious, neoplastic or immunologic 35. In our patient, there was no evidence of any infectious or neoplastic process as evidenced by the serological testing, viral amplification methods and the biopsy.…”
Section: Discussionmentioning
confidence: 58%
“…The disappearance of the bile ducts is a common mechanism for different diseases due to multiple pathologies 2. Conditions which initiate this kind of bile duct destruction could be congenital, idiopathic, toxin or drug induced, infectious, neoplastic or immunologic 35. In our patient, there was no evidence of any infectious or neoplastic process as evidenced by the serological testing, viral amplification methods and the biopsy.…”
Section: Discussionmentioning
confidence: 58%
“…[33]1NoNoNoHepatic failureBarta S.K. [34]1YesFullNoCureDeBenedet A.T. [35]1YesReducedNoHepatic failureLeeuwenburgh I. [36]1YesReducedNoCurePass A.K.…”
Section: Resultsmentioning
confidence: 99%
“…Chemotherapy with nitrogen mustard agents and steroids may be considered in the setting of liver failure, and there have been successful reports with this approach in HL patients with hepatic dysfunction [11,15]. This treatment approach was employed for our patient, with marked improvement initially in his liver and renal dysfunction.…”
Section: An Unusual Presentation Of Liver Failure In a Patient With Pmentioning
confidence: 91%
“…Primary GI HL involving the bowel has been associated with inflammatory bowel disease (IBD) in several case reports [9][10][11][12]. Kumar et al reported 4 cases of GI HL with concurrent EBV infection, with two of the cases occurring in patients with Crohn's disease.…”
Section: An Unusual Presentation Of Liver Failure In a Patient With Pmentioning
confidence: 99%